Exome Sequencing of an Adult Pituitary Atypical Teratoid Rhabdoid Tumor - Biswas, Swethajit; Wood, Madeleine; Joshi, Abhijit; Bown, Nick; Strain, Lisa; Martinsson, Tommy; Campbell, James; Ashworth, Alan; Swain, Amanda (Frontiers in Oncology, 2015)
Atypical teratoid rhabdoid tumors (AT/RTs) are rare pediatric brain tumors characterized by bialleic loss of the SMARCB1 tumor suppressor gene. In contrast to pediatric AT/RT that has a simple genome, very little is known about the adult AT/RT genomic landscape. Using a combination of whole-exome sequencing and high-resolution SNP array in a single adult pituitary AT/RT, we identified a total of 47 non-synonymous mutations, of which 20 were predicted to cause non-conservative amino acid substitutions, in addition to a subclone of cells with trisomy 8. We suggest that adult AT/RT may not be markedly dissimilar to other adult brain tumors where mutations in a range of genes, reflecting the functional specialization of different brain regions, but including SMARCB1 inactivation, may be required for its pathogenesis.